Konkurencyjność polskich metropolii a konkurencyjność regionów - Markowska-Przybyła, Urszula (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
Contemporary processes of globalization emphasize particularly intensive spatial dimension of human activity. The spatial dimension - passed over for a number of years in economics - comes back in t his connection anew. A lot of questions appear, and among them: does globalization cause even greater disparities, do processes of competition deepen polarization? Ts it possible for globalization to become a chance to break growing disproportion? The answer to that question should take into consideration numerous aspects. The author made an attempt to formulate partial reply in present paper. Two essential dimensions of globalization: metropolization and growing competition were presented. An empirical verification of these twa aspects was undertaken on a basis of the example of Polish metropolises. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1143, s. 221-228